Pneumomediastinum following a dental procedure - Al-Kaisy, Maythem Abdulhassan; Al-Shaibani, Noura Ishaq; Fazallulah, Mohammad (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Subcutaneous emphysema is a common presentation to the emergency department. The presence of emphysema in the head and neck region due to dental procedure is not common, and the presence of pneumomediastinum is exceedingly rare.Case Report: A young lady, presented to the emergency department with chest pain, found to have pneumomediastinum following a dental procedure including a wisdom tooth extraction.Conclusion: Complications following dental procedures are not uncommon, hence there should be a high index of suspicion for the emergency physicians for such patients, especially those where air turbine dental tools have been used.